The Influence of socio cultural and educational background on EFL learners' motivation - Meta Keumala; Nanda Marlina Samad; Iskandar Abdul Samad; Noor Rachmawaty (Institut Agama Islam Negeri Palopo, 2019)
Abstract: It is undeniable that motivation plays a very important role in the learning process of students. However, some learners still face difficulties in learning English language due to some factors such as differences on its cultural aspects that contributes to the lack of intercultural competence on EFL learners. The aim of the research is to investigate the socio cultural and educational factors that influence the learner’s motivation on English as a Foreign Language (EFL) learning among post-graduate students of English Department of Syiah Kuala University, Aceh, Indonesia. The method of the study is descriptive qualitative where researchers collected the data through library research and distribution of questionnaires to twenty students. The results showed that socio cultural and educational background impact on learners’ motivation in EFL learning. Students who are in collectivistic culture (60%) carried traditional thinking in facing new culture during the EFL learning process while the rest of the students who are in the part of individualistic culture (40%) tend to react positively in facing new culture. Furthermore, educational background also has impacted the learners’ motivation. Students’ prior knowledge contribute to (70%) their learning achievement.